2021
DOI: 10.1016/j.cmi.2021.07.030
|View full text |Cite
|
Sign up to set email alerts
|

Rate and severity of suspected SARS-Cov-2 reinfection in a cohort of PCR-positive COVID-19 patients

Abstract: Objectives To estimate the burden and severity of suspected reinfection with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). Methods A retrospective cohort of members of Kaiser Permanente Southern California with PCR-positive SARS-CoV-2 infection between 1st March 2020 and 31st October 2020 was followed through electronic health records for subsequent positive SARS-CoV-2 tests (suspected reinfection) ≥90 days after initial infection, through 31st January 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
43
3

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(53 citation statements)
references
References 13 publications
7
43
3
Order By: Relevance
“…In particular, the surveillance of healthcare workers in the U.K. [ 1 , 2 ] and Denmark [ 3 ], carried out in 2020 (i.e., before vaccinations began), showed that from 0.15% to 0.87% of patients who were seropositive after the initial COVID-19 infection were reinfected within about 6 months of follow-up. Similar data were obtained for a large cohort of patients (not at risk) in the USA [ 4 ]; approximately 0.8% had a new positive PCR test for SARS-CoV-2 within 270 days (but not before 90 days) after initial recovery. Furthermore, patients with reinfection were more likely to need hospital admission than patients with primary COVID-19 [ 4 ].…”
Section: Introductionsupporting
confidence: 78%
See 2 more Smart Citations
“…In particular, the surveillance of healthcare workers in the U.K. [ 1 , 2 ] and Denmark [ 3 ], carried out in 2020 (i.e., before vaccinations began), showed that from 0.15% to 0.87% of patients who were seropositive after the initial COVID-19 infection were reinfected within about 6 months of follow-up. Similar data were obtained for a large cohort of patients (not at risk) in the USA [ 4 ]; approximately 0.8% had a new positive PCR test for SARS-CoV-2 within 270 days (but not before 90 days) after initial recovery. Furthermore, patients with reinfection were more likely to need hospital admission than patients with primary COVID-19 [ 4 ].…”
Section: Introductionsupporting
confidence: 78%
“…Similar data were obtained for a large cohort of patients (not at risk) in the USA [ 4 ]; approximately 0.8% had a new positive PCR test for SARS-CoV-2 within 270 days (but not before 90 days) after initial recovery. Furthermore, patients with reinfection were more likely to need hospital admission than patients with primary COVID-19 [ 4 ]. Among healthcare workers in Chicago, USA [ 5 ], up to 2.5% presented a probable reinfection within 6 months of follow-up.…”
Section: Introductionsupporting
confidence: 78%
See 1 more Smart Citation
“…de Candia et al proposed that naive repertoires exert better control by virtue of greater TCR repertoire diversity which historically is associated with lower CD4 and CD8 T cell activation ( 38 ). however no model reconciles 1) the low Case Fatality Rate (CFR) seen in children ( 24 , 25 ); 2) the high CFR seen in the elderly ( 39 ); 3) cases of more severe reinfection ( 40 ); 4) the efficacy of steroids, which cause a rapid reduction in CD8+ T-cells, and suppress Fas and FasL in T-cells ( 41 45 ); 5) the efficacy of anti GM-CSF ( 46 , 47 ), which downregulates Fas expression on T-cells ( 48 ); and the high degree of Fas-mediated T cell apoptosis which characterizes severe Covid-19 ( 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…Considering the reinfection of convalescent individuals, an Austrian retrospective study (n = 14,840) reported a relatively low reinfection rate (0.27%) among individuals with COVID-19 and deduced that protection against SARS-CoV-2 following a natural infection is comparable to the highest available estimates of vaccine efficacy [19]. Comparable results were also yielded by another retrospective study [20] from California with a sample size of n = 75,149, where the overall incidence of reinfection after 270 days was as low as 0.8%. Likewise, a prospective Italian study (n = 546) investigated reinfection rates of SARS-CoV-2 up to ten months post infection.…”
Section: Immunity After Sars-cov-2 Infection Versus Post Vaccinationmentioning
confidence: 91%